Beyond the western crime drop: violence, property offences, and the state in Turkey 1990-2016 - Atak, Kıvanç (International journal of law, crime and justice, 2020)
Temporal changes in crime have long attracted scholarly attention. Much research on the recent trajectory of crime rates is dominated by the crime drop thesis in western democracies, with only little input from other societal contexts. The present work offers the first explorative inquiry into a subset violent and property crimes in Turkey over the last quarter-century. Data collected from judicial records, police reports on offences, prison and causes of death statistics are read primarily through the lens of state response to crime, with the notable exception of homicide. Results reveal partial evidence for a declining behavioral trend in the case of homicide - a finding that furthers current debates about the crime drop thesis. Rather mixed evidence is documented for robbery, theft and assault, but a common marked increase in the number of offences, suspects and convicts received into prison. Implications are discussed by reference to the emergent punitive turn in the Turkish penal regime, and enhanced police capacity to control crime.